ANTIOXIDANT AND ANTIMICROBIAL ACTIVITIES OF JORDANIAN SIMMONDSIA CHINENSIS (LINK) C.K. SCHNEID - Hani AL-Qizwini; Ekbal AL-Khateeb; Nizar M. Mhaidat; Anwar Maraqa (European Scientific Journal, ESJ, 2014)
Context: Various parts of Jojoba plant have been used in ethnomedicine for skin disorders, wound healing and many others. Objective: The purpose was to examine the effect of the total extracts of Jojoba leaves (male & female), testa, seeds and oil on the growth of certain microorganisms in addition to evaluating the antioxidant activity of these extracts. Materials and methods: Plant parts were subjected for hot extraction by solvents of different polarity (hexane, methanol and ethanol) in addition to cold pressing extraction for seed. Furthermore, the active compounds were isolated by preparative thin layer chromatography, followed by identification for simmondsin and three of its derivatives namely Simmondsin-3’-ferulate, 4, 5-Didemethylsimmondsin and 4-Demethylsimmondsin-2’- ferulate, in addition to phenolic compounds, phytosterols, toccopherols and fatty acids. This was accomplished using chemical reagents along with various methods of chromatography and spectral analysis. The evaluation of antioxidant activity of extracts was done by 2, 2-Diphenyl-1-pircryl hydrazyl (DPPH) free radical scavenging method comparing to ascorbic acid activity. Antibacterial and antifungal activities were done using two methods; the agar well diffusion and disc diffusion methods, against (Staphylococcus aureus, Bacillis subtilis, Escherichia coli, Klebsiella pneumonia and Candida albicans). Results: The methanolic extract of testa and ethanolic extracts of both male and female leaves all possess antioxidant activity. Crude extracts do not exhibit antimicrobial activity, neither antibacterial nor antifungal activity. Discussion and conclusion: Plant extracts induced variable degrees of antioxidant activity and proposes its potential as an antioxidant agent for pharmaceutical applications. However, they do not have antimicrobial activity.